Gen Z OCB: Ethical Leadership’s Impact via Ethical Climate and Organizational Commitment in Indonesia’s Manufacturing - Ratih Anggraini; Sun Bun; Ferdinand Nainggolan (Goodwood Publishing, 2026)
Purpose: This study investigates the influence of ethical leadership on Organizational Citizenship Behavior (OCB) among Generation Z employees in Indonesia's manufacturing industry. Its key novelty lies in the simultaneous examination of ethical climate and organizational commitment as dual mediators, an approach rarely explored among Gen Z workers in the manufacturing sector of a developing economy, addressing a critical gap in the organizational behavior literature. Research Methodology: A survey of 350 Generation Z employees (aged 21–27) from manufacturing companies in Batam City was conducted via online questionnaire (Google Forms) from November 2024 to February 2025. Data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) using SmartPLS 4.0. Results: Ethical leadership positively and significantly influenced the ethical climate and organizational commitment. Both mediators positively and significantly influenced organizational citizenship behavior. Organizational commitment is a stronger mediator than ethical climate in linking ethical leadership to OCB. The research model strongly predicted OCB. Conclusions: Manufacturing firms should invest in ethical leadership development, transparent ethical policies, and emotional bonds with Generation Z employees to improve talent retention and organizational performance. Limitations: The findings are limited to Generation Z employees in Batam's manufacturing sector, potentially restricting generalizability to other regions, industries, or generational cohorts in Indonesia. Contributions: These findings help manufacturing managers and HR practitioners leverage ethical leadership to boost OCB through organizational commitment and an ethical climate. Theoretically, this study advances organizational behavior research by validating dual mediation in an underexplored Indonesian industrial context.